Measuring privatisation in education: methodological challenges and possibilities. Issue 1 (2nd January 2019) - Winchip, Emily; Stevenson, Howard; Milner, Alison
ABSTRACT: As the Global Education Reform Movement (GERM) spreads, key questions that attempt to identify both the nature and the increasing scope and scale of this phenomenon become empirically significant. The concern of this article is to highlight some of the complexities of measuring one key element of the GERM: the privatisation of public education systems. Exploring indicators of privatisation through a set of methods for analysing Likert-style data, Mokken scale analysis and Rasch analysis, we generate a scale to measure an educational phenomenon so complex that it can appear to defy measurement. Our intention is to demonstrate that complex phenomena should not be oversimplified for the purpose of generating numeric data and that measurement is possible. The results, drawn from a European-wide survey, portray a nuanced pattern of privatisation at this regional level in which public funding and ownership remain important, but schools are commonly adopting a wide range of "private-like" practices.